Mapping the Galactic Disk with the LAMOST and Gaia Red Clump Sample. VIII. Mapping the Kinematics of the Galactic Disk Using Mono-age and Mono-abundance Stellar Populations - Sun, Weixiang; Huang, Yang; Shen, Han; Wang, Chun; Zhang, Huawei; Tian, Zhijia; Liu, Xiaowei; Jiang, Biwei (The Astrophysical journal, 2024)
We present a comprehensive study of the kinematic properties of the different Galactic disk populations, as defined by the chemical abundance ratios and stellar ages, across a large disk volume (4.5 ≤ R ≤ 15.0 kpc and ∣ Z ∣ ≤ 3.0 kpc), by using the LAMOST-Gaia red clump sample stars. We determine the median velocities for various spatial and population bins, finding large-scale bulk motions; for example, the wave-like behavior in radial velocity, the north–south discrepancy in azimuthal velocity and the warp signal in vertical velocity, and the amplitudes and spatial dependences of these bulk motions show significant variations for different mono-age and mono-abundance populations. The global spatial behaviors of the velocity dispersions clearly show a signal of spiral arms and a signal of the disk perturbation event within 4 Gyr, as well as disk flaring in the outer region (i.e., R ≥ 12 kpc), mostly for young or alpha-poor stellar populations. Our detailed measurements of age/[ α /Fe]-velocity dispersion relations for different disk volumes indicate that young/ α -poor populations are likely to originate from dynamic heating by both giant molecular clouds and spiral arms, while old/ α -enhanced populations require an obvious contribution from other heating mechanisms, such as merger and accretion, or are born in the chaotic mergers of gas-rich systems and/or turbulent interstellar medium.